EFEKTIVITAS PROGRAM BANTUAN SOSIAL TUNAI PADA MASA PANDEMI COVID-19 DI KELURAHAN PASIR PENGARAIAN - Melati Melati; Zulkarnaini Zulkarnaini (Universitas Halu Oleo, 2021)
The Cash Social Assistance Program (BST) is assistance sourced from the Ministry of Social Affairs of the Republic of Indonesia which will be provided to the community based on Integrated Social Welfare Data (DTKS). The purpose of this research is to find out how the effectiveness of the implementation On Social Cash Assistance program during the Covid-19 pandemic in Pasir Pengaraian Village and to find out what are the factors that hinder the implementation of the BST program. The theory used in this research is the theory of program effectiveness by Budiani using 4 indicators (Accuracy of Target, Program Socialization, Program Objectives, Program Monitoring). To be able to answer these problems the researcher used a qualitative method with a descriptive approach / in this qualitative research the writer used data collection techniques in the form of interviews, observation and documentation then analyzed based on the research problem. The results of this study indicate that the effectiveness of the implementation On Social Cash Assistance program during the Covid-19 pandemic in Pasir Pengaraian Village is seen from 4 indicators (Accuracy of Target, Program Socialization, Program Objectives, Program Monitoring) have not been effective. The inhibiting factors in this study were data validation and programs that were issued suddenly.